Risk Menejemen E–Bekal untuk Meningkatkan Pelayanan pada Santri di Pondok Pesantren Nurul Jadid - Saifuddin Saifuddin; Alvan Fathony (Reslaj : Religion Education Social Laa Roiba Journal, 2023)
The digital economy has changed the global economy with the existence of electronic money which is currently a very popular average payment that is used by all circles, especially among Islamic boarding schools. Nurul Jadid Islamic Boarding School is one of the boarding schools that implements electronic money (e-money) as a medium of payment, although in its use there are still many obstacles and risks. This study wants to know and analyze what are the risks involved in the use of electronic money and how to overcome them. The method used in this research is descriptive qualitative with a phenomenological approach and data collection. The results of this research conclude that the use of electronic money makes it easier for students to make transactions even though there are still risks and obstacles in their use, in this case the Islamic boarding school tries to overcome this problem, the aim is to improve services to students. Keywords: management, e-money, e-bekal